Infrared and Raman spectroscopic features of plant cuticles: a review - Heredia-Guerrero, José A.; Benítez, José J.; Domínguez, Eva; Bayer, Ilker S.; Cingolani, Roberto; Athanassiou, Athanassia; Heredia, Antonio (Frontiers in Plant Science, 2014)
The cuticle is one of the most important plant barriers. It is an external and continuous lipid membrane that covers the surface of epidermal cells and whose main function is to prevent the massive loss of water. The spectroscopic characterization of the plant cuticle and its components (cutin, cutan, waxes, polysaccharides and phenolics) by infrared and Raman spectroscopies has provided significant advances in the knowledge of the functional groups present in the cuticular matrix and on their structural role, interaction and macromolecular arrangement. Additionally, these spectroscopies have been used in the study of cuticle interaction with exogenous molecules, degradation, distribution of components within the cuticle matrix, changes during growth and development and characterization of fossil plants.